Thermodynamics of the solid solution - Aqueous solution system (Ba, Sr, Ra)SO4 + H2O: II. Radium retention in barite-type minerals at elevated temperatures. (June 2018) - Vinograd, V.L.; Kulik, D.A.; Brandt, F.; Klinkenberg, M.; Weber, J.; Winkler, B.; Bosbach, D.
Abstract: The effect of temperature on the solid solution – aqueous solution (SS-AS) equilibria in the (Ba, Sr, Ra)SO4 +H2 O system is primarily determined by a change in the aqueous solubilities of the end members BaSO4, SrSO4 and RaSO4. The dependence of the solubility vs. the temperature for an MSO4 sulphate is, in turn, determined by the entropy and the heat capacity effects of the reaction MSO4 = M 2+ + SO4 2− . The missing data for M = Ra are estimated here by a combination of atomistic simulations, a Debye-Einstein extrapolation of known thermodynamic properties of MSO4 sulphates, direct experimental measurements of solid solubility in the system (Ba, Ra)SO4 +H2 O at 70 and 90 °C, and thermodynamic modelling with the aid of the GEM-Selektor code. Finally, the GEM simulations together with the data assessed here and in Part I of this study (Vinograd et al. 2017) are applied to model the uptake of Ra in the (Ba, Sr, Ra)SO4 +H2 O system in the temperature range of 0–300 °C. Our results, consistent with earlier studies, show that the uptake of Ra by (Ba, Sr)SO4 barite solid solutions at about 25 °C is favoured by a lower solubility of RaSO4 relative to those of BaSO4 and SrSO4, however, with increasing temperature, the solubilities of MSO4 solids converge. Consequently, an increase in temperature makes the Ra uptake by Ba, Sr sulphates less efficient. In a radioactive waste repository relevant system, this effect would be partially compensated by the common anion and the dilution effects, which both enhance the Ra-uptake.